The theory of endobiogeny. - Hedayat, Kamyar M.; Lapraz, Jean-Claude (Academic Press, 2019)
The Theory of Endobiogeny Volume 1: Global Systems Thinking and Biological Modeling for Clinical Medicine offers researchers and clinicians a detailed introduction to the theory of Endobiogeny. The book presents a new approach to medicine that is at once scientific and humanistic, quantitative, and qualitative. The philosophical and experimental basis of a global complex systems approach to physiology is presented along with a mathematical approach to modeling the dynamism of the terrain. The importance of the history and physical examination are renewed as a source of "big data readily available to clinicians for greater insight into the patient's state. Expansion of the therapeutic compendium is proposed based on a rational, clinical approach correlated to mathematical indicators of the physiologic state. What is proposed in this work is a fundamental shift in scientific thinking with a resulting expansion of the boundaries of clinical medicine for the 21st century and beyond. Extends systems biology from the cellular to the integrative physiologic levelMoves the functional medicine approach to a higher level of integration and true global systems thinkingPresents mathematical tools and proofs of formulas related to the biology of functions: a biological modeling system based on the theory of endobiogeny. The biology of functions has assisted clinicians in conceptualizing, treating, and objectively monitoring the longitudinal effects of treatment through the evolution of the patient's unique phenotypic expression of terrain